Association between serum antibodies against oral microorganisms and vitamin D deficiency among US adults - Li Tan; Si-qun Xu (Medicine, 2026)
Vitamin D deficiency is common and may contribute to periodontal disease by affecting periodontal pathogens. Most studies analyzing this association have focused mainly on a specific periodontal bacterium ( P gingivalis ) and have involved relatively small study populations (tens or hundreds of individuals). To address this gap, a sizable, nationally representative adult population was utilized to investigate the association between the prevalence of Vitamin D deficiency and immunoglobulin G (IgG) antibodies to 19 periodontal bacteria using a large, nationally representative population. Drawing from the Third National Health and Nutrition Examination Survey, which constitutes a cross-sectional representation of the noninstitutionalized US population encompassing 33,994 individuals, we incorporated all qualifying participants aged 40 and above. These participants were then categorized into 2 groups according to serum 25-hydroxyvitamin D (25 [OH]D) concentration levels, following the Endocrine Society Clinical Practice Guidelines: Vitamin D deficiency (